Toward an Injectable Continuous Osmotic Glucose Sensor - Johannessen, Erik (Diabetes Technology Society, 2010)
BACKGROUND: The growing pandemic of diabetes mellitus places a stringent social and economic burden on the society. A tight glycemic control circumvents the detrimental effects, but the prerogative is the development of new more effective tools capable of longterm tracking of blood glucose (BG) in vivo. Such discontinuous sensor technologies will benefit from an unprecedented marked potential as well as reducing the current life expectancy gap of eight years as part of a therapeutic regime. METHOD: A sensor technology based on osmotic pressure incorporates a reversible competitive affinity assay performing glucose-specific recognition. An absolute change in particles generates a pressure that is proportional to the glucose concentration. An integrated pressure transducer and components developed from the silicon micro- and nanofabrication industry translate this pressure into BG data. RESULTS: An in vitro model based on a 3.6 × 8.7 mm large pill-shaped implant is equipped with a nanoporous membrane holding 4–6 nm large pores. The affinity assay offers a dynamic range of 36–720 mg/dl with a resolution of ±16 mg/dl. An integrated 1 × 1 mm(2) large control chip samples the sensor signals for data processing and transmission back to the reader at a total power consumption of 76 µW. CONCLUSIONS: Current studies have demonstrated the design, layout, and performance of a prototype osmotic sensor in vitro using an affinity assay solution for up to four weeks. The small physical size conforms to an injectable device, forming the basis of a conceptual monitor that offers a tight glycemic control of BG.